The Role of Cash-Waqf Capital Ventures to Supply Shock Liquidity of Sharia Banks in East Java: Multivariate Threshold Autoregressive Simulation Model - Fadili; Renita Nur Pratiwi (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2020)
Adequacy of liquidity is very important for Islamic banks to carry out their main functions as Islamic financial intermediaries and provide financing for the real sector. However, many Islamic banks are proven to have a shock in providing liquidity due to the weak capital structure of the bank. While cash-waqf funds can be a potential source of capital for sharia banks if managed as capital investments in sharia banks with a mudharabah or musyrakah contract. Therefore, using the autoregressive multivariate threshold simulation model approach, this study attempts to analyze the dynamic interaction between the monetary policy regime, cash-capital capital ventures, Islamic bank liquidity and inflation in East Java. The participation of waqf funds on Islamic bank capital is simulated at 1%, 5% and 10% with two regimens of threshold models, namely a tightening monetary policy regime and a monetary policy easing regime. The data in this study were obtained from Statistik Perbankan Syariah (SFS) published by the OJK and BI with the observation period of 2014.M1 - 2018.M6. The results show that the inclusion of waqf funds in Islamic bank capital is able to reduce the length of the period and the sharia bank liquidity shock both in high interest rate policy regime and low interest rate regime.